Presentation Article - World Puppetry: Konstantina Sofokleous - Sofokleous, Konstantina (My University, 2026)
Presentation Article for Konstantina Sofokleous in the World Puppetry Section Puthalika Patrika, International Puppetry Magazine January 2026 Publication
Keywords: Arts and entertainment